Controle da brusone do trigo : reação de genótipos e desempenho de fungicidas em ambiente controlado - Silva, Daniela da (2025)
Wheat blast, caused by Pyricularia oryzae Triticum (PoT), is one of the main diseases affecting wheat crops. Given the economic and social impact of the disease, the search for effective management strategies is a priority in studies on this pathosystem. In this work, we investigate, based on different studies, the sporulation capacity of PoT, resistance to blast in young and adult plant stages, virulence of PoT isolates, as well as the efficiency of fungicides in controlling the disease, evaluating aspects such as seedling protection and systemic action on wheat leaves and ears. Understanding these aspects is essential for establishing integrated strategies for managing wheat blast. Thus, we reached the following results: Cultivars such as ORS 1403 and TBIO Aton, with lower sporulation of PoT in leaves, can reduce the availability of inoculum in the environment and the spread of the disease. Genotypes such as ORS Feroz and PF 190018 stood out for presenting greater resistance to leaf and ear blast, contributing to the development of more resistant cultivars. The interaction between different PoT isolates and wheat genotypes varies significantly, reinforcing the need for continuous monitoring of pathogen diversity for the development of resistant cultivars. The combination of moderately resistant cultivars with seed treatment using fungicides such as Triadimenol is important for seedling protection. In addition, the efficacy of fungicides in controlling leaf blast depends on the type of product and inoculum concentration, with Propiconazole and Mancozeb presenting the best results. Fungicides such as Cyproconazole, Flutriafol, Propiconazole, Pidiflumetofen and Tebuconazole demonstrate greater systemicity and lower severity of blast in wheat ears, indicating the possibility of applying these products to the aerial part of the plant for disease control. Understanding the different management strategies for controlling wheat blast and how these affect the response of wheat genotypes inoculated with the pathogen is important for establishing integrated management programs in the context of this pathosystem.